Pendampingan Pemanfaatan Limbah Sekbuk Kayu dalam Memperoleh Value Added yang Bernilai Ekonomis - Amrussalam Amrussalam; Fitry Ariyanti (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
UD. Tabola Mebel is a type of Micro, Small, and Medium Enterprises (MSME) engaged in furniture which is located in the Kemutar Telu RT 03/RW 08, Menala Village, Taliwang District, West Sumbawa Regency, NTB, with services based on orders from consumers for various types of furniture, ranging from chairs to chairs. , desk, wardrobe, and bed. The purpose of the Stimulus Community Partnership Program is to provide knowledge and skills to partners, both to those in charge & managers and their workers, in order to obtain design of quality wood sawdust waste utilization, so that it can function properly at the production level to produce performance of product that has economic value. The implementation method in this program is using PALS, which consists of 3 (three) stages, namely awareness, participation and training and mentoring. The results and outputs of the Stimulus Community Partnership Program are increased knowledge and skills of Partners on the potential and performance of a process in the utilization of sawdust waste into products of economic value, namely the design of paving block products.